2015
DOI: 10.1103/physrevb.91.235304
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic structures and electronic energy levels at reconstructed NiO(111) surfaces: ADFT+Ustudy

Abstract: ABSTRACT:We studied how the surface reconstruction and passivation influence the antiferromagnetic and electronic structures of NiO(111) surface using first-principles electronic structure calculations. These features lead to a surprisingly wide variety of different surface electronic structures, and some surfaces are even metallic. Different reconstructions and surface passivation were also found to qualitatively alter the charge-transfer band gap type of bulk NiO. At the same time, the antiferromagnetic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…First-principles calculations using density functional theory with the Hubbard correction (DFT + U) closely follow the computational details, as described in the previous work. 40 DFT + U calculations were performed using the Quantum Espresso code. 41 The interaction of the valence electrons with ionic cores was described by the Vanderbilt ultrasoft pseudopotentials, 42 and the Kohn−Sham wavefunctions were represented in a plane-wave basis set, where the energy cutoffs of the wavefunctions and the density were 30 and 300 Ry, respectively.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First-principles calculations using density functional theory with the Hubbard correction (DFT + U) closely follow the computational details, as described in the previous work. 40 DFT + U calculations were performed using the Quantum Espresso code. 41 The interaction of the valence electrons with ionic cores was described by the Vanderbilt ultrasoft pseudopotentials, 42 and the Kohn−Sham wavefunctions were represented in a plane-wave basis set, where the energy cutoffs of the wavefunctions and the density were 30 and 300 Ry, respectively.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…First-principles calculations using density functional theory with the Hubbard correction (DFT + U ) closely follow the computational details, as described in the previous work . DFT + U calculations were performed using the Quantum Espresso code .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On top of this, in such a treatment, the passivation of the surface has to be done atom by atom and it might have a significant effect on the electronic properties (and the calculated gap) of the material. This becomes evident in the thorough and extensive DFT + U investigation of (111) NiO surface by Li et al [ 24 ], which revealed that the calculations on three slabs with different thicknesses (1.43, 1.92, and 2.41 nm) produced the same gap which, by the way, is also smaller than the calculated bulk gap (2.43 eV). As a result, we resort to the traditional and well behaved combination of HF and EMA, which has a proven record of successful treatments of such problems.…”
Section: Introductionmentioning
confidence: 89%
“…For the surfaces covered with Ni n or (NiO) n clusters, a Hubbard U term acting on Ni 3 d orbitals was added to the standard PBE functional to describe the static electronic correlation effect [43] . DFT + U method has been successfully used to calculate surface structure, stability, electronic structure, and gas adsorption on different surfaces of NiO [44][45][46][47] . We applied the U eff ( = U − J ) of 5.3 eV on Ni 3 d states according to the reported values in literatures [4 8,4 9] .…”
Section: Methodsmentioning
confidence: 99%